Transformational Leadership by Department Heads in Enhancing the Digital Competencies of Civil Servants - Baety Asifa; Mukarto Siswoyo (Salus Publica: Journal of Community Service, 2026)
Digital transformation in the field of public administration needs high digital competences in civil servants, where leadership becomes a key in this process. This research tries to build up analysis of transformational leadership of the department head in enhancing the digital competences of civil servants, the barriers found, and how the barriers have been overcome. The research was conducted through qualitative research with semi-structured interviews on three informants, namely department head, structural officers, and civil servants of the Cirebon City Department of Cooperatives, SMEs, Trade and Industry. The results of this research prove that the transformational leadership of the Department Head can be seen from the exemplary use of digital technology, consistent vision and motivation communication, innovation, and differences in digital competence of civil servants. Nevertheless, there are some barriers for enhancing digital competencies, which consist of the gaps in digital literacy between employees, a lack of internal training programs, and technological barriers. According to the findings of this study, it is possible to say that transformational leadership plays an important role in promoting the enhancement of digital competencies of civil servants; however, for increasing the effectiveness of this strategy, it should be supported by a continuous training program and technological infrastructure.